La ocupación del espacio en el territorio urbano del sector San Antonio de la ciudad de Riobamba, en el periodo 2000-2019. - Quishpe Ponce, Dayci Sthefanny (2022)
This study is focused on the urban growth of Riobamba. The study base is the "San Antonio del Aeropuerto" neighborhood located north of the city. The research analyzes three aspects: The process of land occupation, after the division of the San Antonio farm; the urbanization of the sector that is linked to the organization and actions of the inhabitants; and finally, urban functions are described, in addition, an emphasis in economic activities.This research is non-experimental - longitudinal, and geographically descriptive with a qualitative approach. Besides, data were collected through bibliographic reviews, analysis of primary sources, direct observation, surveys, interviews, and cartographic interpretation.The results show that the use of the land in the perimeter of Riobamba was modified by the decision of the former owners of the land, who for economic purposes segmented the farm. In the period 2000 - 2019, this place has had a considerable urban growth, showing communication routes, supply of basic services and foundations of equipment. With the organization of the inhabitants, the “San Antonio del Aeropuerto” neighborhood is legally formed. Beginning a slow process of urbanization. The area is considered an urban attraction after the construction of two places of affluence such as: “Universidad Nacional de Chimborazo” and, “Paseo Shopping Riobamba” This has influenced the capital gains of this site to grow. In this place some activities have been developed such as: hire of house or apartments, besides others.